2018
DOI: 10.1017/qua.2018.31
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the function of prehistoric stone bowls and griddle stones in the Aleutian Islands by lipid residue analysis

Abstract: The earliest durable cooking technologies found in Alaska are stone bowls and griddle stones recovered from the Aleutian Islands. This article aims to identify the function of these artefacts. Molecular and chemical analyses of carbonised residues found on their surfaces confirm that these artefacts were used to process marine resources. Both artefacts have high lipid content and C:N ratios, suggesting they were used to process oily substances. Stable isotope results of individual lipids suggest that they were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 36 publications
1
8
0
Order By: Relevance
“…This approach has provided valuable insights into human activities, technology and economies (Heron and Evershed 1993;Evershed 2008;Regert 2017). The identification of specific lipid markers (biomarkers) using gas chromatography-mass spectrometry (GC-MS) has been used to track a range of commodities in ancient pottery, such as aquatic resources (Copley et al 2004;Lucquin et al 2016b;Gibbs et al 2017;Shoda et al 2017;Admiraal et al 2019;Bondetti et al 2020), beehive products (Roffet-Salque et al 2015;Shoda et al 2018), edible plants (Dunne et al 2016;Heron et al 2016;Bondetti et al 2020), and various types of resins, wood tars and pitches (Heron et al 1994(Heron et al , 2015Mitkidou et al 2008;Rageot 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This approach has provided valuable insights into human activities, technology and economies (Heron and Evershed 1993;Evershed 2008;Regert 2017). The identification of specific lipid markers (biomarkers) using gas chromatography-mass spectrometry (GC-MS) has been used to track a range of commodities in ancient pottery, such as aquatic resources (Copley et al 2004;Lucquin et al 2016b;Gibbs et al 2017;Shoda et al 2017;Admiraal et al 2019;Bondetti et al 2020), beehive products (Roffet-Salque et al 2015;Shoda et al 2018), edible plants (Dunne et al 2016;Heron et al 2016;Bondetti et al 2020), and various types of resins, wood tars and pitches (Heron et al 1994(Heron et al , 2015Mitkidou et al 2008;Rageot 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown a correspondence between the bulk δ 13 C values of carbonized residues and absorbed lipids, where the combination of analyses have provided complementary data to support conclusions regarding vessel use 35 40 . For example, both bulk δ 13 C values and individual fatty acid δ 13 C values can discriminate between habitats, such as terrestrial versus aquatic species (and further refinement between freshwater, marine, and anadromous species), since marine species are 13 C enriched 35 39 , 41 .…”
Section: Introductionmentioning
confidence: 99%
“…In Admiraal et al (2018), the incorrect article information was given for the in-text citation of Oras et al, 2017. The correction reference is as follows:…”
mentioning
confidence: 99%